REPRESENTASI MAKNA MATERIALISME PADA VIDEO KLIP LAGU MONEY - Jeanie Annissa; Ricky Widyananda Putra (ADISAM PUBLISHER, 2024)
This paper discusses about the analysis of the meaning of materialism in the video clip of the song